2015
DOI: 10.1021/jacs.5b03322
|View full text |Cite
|
Sign up to set email alerts
|

Domino Tunneling

Abstract: Matrix-isolation experiments near 3 K and state-of-the-art quantum chemical computations demonstrate that oxalic acid [1, (COOH)2] exhibits a sequential quantum mechanical tunneling phenomenon not previously observed. Intensities of numerous infrared (IR) bands were used to monitor the temporal evolution of the lowest-energy O-H rotamers (1cTc, 1cTt, 1tTt) of oxalic acid for up to 19 days following near-infrared irradiation of the matrix. The relative energies of these rotamers are 0.0 (1cTc), 2.6 (1cTt), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 82 publications
0
45
0
2
Order By: Relevance
“…This might on the one hand be due to the IR Globar irradiation from the spectrometer (the activation barrier for the reverse reaction 2 ct → 2 tt is only 3.7 kcal mol −1 ). On the other hand, such phenomena have been assigned to matrix effects before, namely that specific matrix environments (or matrix sites) inhibit QMT [50] . Recent precedence is provided in a study on thioacetamide [20] .…”
Section: Resultsmentioning
confidence: 99%
“…This might on the one hand be due to the IR Globar irradiation from the spectrometer (the activation barrier for the reverse reaction 2 ct → 2 tt is only 3.7 kcal mol −1 ). On the other hand, such phenomena have been assigned to matrix effects before, namely that specific matrix environments (or matrix sites) inhibit QMT [50] . Recent precedence is provided in a study on thioacetamide [20] .…”
Section: Resultsmentioning
confidence: 99%
“…[174] The cis-trans isomerization reactions of carboxylic acids were studied extensively. [175][176][177][178][179][180][181][182] These reactions are mostly carried out at cryogenic temperatures in noble gas or N 2 matrix environments.Itwas shown that such an environment can influence the tunneling rates of the isomerization reactions significantly.T his might be taken as ac aveat when comparing with, for example,q uantum chemical gas-phase calculations. [178,179,[183][184][185][186] In larger, bio-organic molecules,t unneling supports radical reactions such as in the autoxidation of tetraline.…”
Section: Organic Chemistrymentioning
confidence: 99%
“…Rotation of the OH group in phenol was shown by FTIR spectroscopy to happen through tunneling, while deuteration of the ortho or meta positions suppresses the tunneling motion at low temperature . The cis–trans isomerization reactions of carboxylic acids were studied extensively . These reactions are mostly carried out at cryogenic temperatures in noble gas or N 2 matrix environments.…”
Section: Impact Of Tunneling On Different Fields Of Chemistrymentioning
confidence: 99%
“…45 To achieve highquality fits of the data within the experimental error bars, the assumption of three classes of matrix-isolated carbonic acid molecules was required: a frozen class, in which tunnelling is entirely precluded by the environment; a slow class with seemingly hindered conformational tunnelling and half-lives (t 1 ) of 11-26 h; and a fast class, characterized by half-lives (t 2 ) of 2-5 h, for which the matrix atoms appear to interfere to only a limited extent with the conformational tunnelling. 45 To achieve highquality fits of the data within the experimental error bars, the assumption of three classes of matrix-isolated carbonic acid molecules was required: a frozen class, in which tunnelling is entirely precluded by the environment; a slow class with seemingly hindered conformational tunnelling and half-lives (t 1 ) of 11-26 h; and a fast class, characterized by half-lives (t 2 ) of 2-5 h, for which the matrix atoms appear to interfere to only a limited extent with the conformational tunnelling.…”
mentioning
confidence: 99%